If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y + 1 = 7y + 5 Reorder the terms: 1 + 5y = 7y + 5 Reorder the terms: 1 + 5y = 5 + 7y Solving 1 + 5y = 5 + 7y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-7y' to each side of the equation. 1 + 5y + -7y = 5 + 7y + -7y Combine like terms: 5y + -7y = -2y 1 + -2y = 5 + 7y + -7y Combine like terms: 7y + -7y = 0 1 + -2y = 5 + 0 1 + -2y = 5 Add '-1' to each side of the equation. 1 + -1 + -2y = 5 + -1 Combine like terms: 1 + -1 = 0 0 + -2y = 5 + -1 -2y = 5 + -1 Combine like terms: 5 + -1 = 4 -2y = 4 Divide each side by '-2'. y = -2 Simplifying y = -2
| -3/2Y=15 | | b^3-7b^2+7b^2-49b-b+7= | | 6y-4=4(y-2) | | 6n-3=-81 | | https://boazk12.instructure.com/courses/848/files/13070/preview | | 7x^2+23x-9=0 | | y+x=141 | | x(x-3)=2x-1 | | 2x-9=-5x+6 | | 0=-5n(-2) | | -(x-4)=2x-5(x+2) | | -5(4r-4)-4r=-172 | | W=150*10 | | -2r-10=-37 | | -15-7z=-14-7z | | (-5m^2-6m-6)-(5m^2+6m+2)= | | 5y+6=6y-5 | | 4x+10=6x-24 | | log9/8 | | 7(x+20)-10=x+4 | | 8t^2+9t-5=0 | | 3(11+3x)=3(-1+5x) | | (z+1)=2(3-2z)+17 | | 16x+10+5x+2=180 | | 32=3x+9 | | (4x-20)= | | y-x=32 | | ((9x-11)+(7x-3))=((4x+1)(4x+1)) | | -9x-3x+4=-10x-(2x-4) | | 288=27x+18 | | 5(2h+3)-4h= | | 90=-5x-5(x-8) |